Kajian Metode dan Waktu Fermentasi Cairan Pulpa pada Perubahan Karakteristik Cuka Kakao - G.P. Ganda Putra; Ni Made Wartini; Luh Putu Trisna Darmayanti (agriTECH, 2017)
The pulp water as byproduct of cocoa beans fermentation is  potential to be used as a raw material for making cocoa vinegar,  but unfortunately the content of acetic acid is relatively low. So  that, it is necessary to increase the content of acetic acid, by  performed further fermentation method with several addition of  carbon sources (sugar and alcohol) and fermentation time. The  purposes of this research were: (1) to study the effect of the  addition of sugar, alcohol and fermentation time on different  urther fermentation method on the characteristics of cocoa vinegar  and (2) to determine the optimal further fermentation  method and fermentation time for the production of cocoa vinegar  with the highest content of acetic acid. Several  fermentation methods were conducted by using three different  methods e.g.the alcoholic and acetic acid fermentation (2 stages),  acetic acid fermentation (1 stage), and fermentation  without inoculum (natural). The experimental design of this study was using a factorial BRD two factors on the 2 stages and the 1 stage fermentation method, as well as the simple RBD on the  natural fermentation. The first factor on the 2 stages fermentation methods used two different inoculum e.g. Saccharomyces  cerevisiae and Acetobacter aceti, 4 different concentration of sugar (4, 6, 8 and 10 %), while on the 1 stage fermentation method  used inoculum Acetobacter aceti, is 4 different concentrations of  alcohol addition (6, 8, 10, and 12 %), while the second factor is  the same, namely 6 levels of fermentation time (0, 5, 10, 15, 20,  and 25 days). Meanwhile, the treatment of fermentation time  on the natural fermentation method was the same as the  second factor. All methods of fermentation were performed at  room temperature in 2 blocks/replications.The results showed  that: 1) the characteristics of cocoa vinegar and OD660 of watery  pulp were affected by : (1) the treatment of the sugar addition  and fermentation time and their interaction on the 2 stages  fermentation method by the treatment of the alcohol addition and  fermentation time, their interaction on the 1 stage  fermentation method, and by the treatment of fermentation time  on the natural fermentation method, and (2) the cocoa vinegar  with the highest content of acetic acid was produced on the 2  stages fermentation method by the addition of 6 % sugar within  25 days (2.35 %), on the 1 stage fermentation method by the   ddition of 10 % alcohol within 20 days (3.37 %), and on the  natural fermentation method within 15 days (2.65 %),  respectively. Our result showed that the 1 stage fermentation  method with the addition of 10 % alcohol using inoculum of  Acetobacter aceti within 20 days is the most optimal further  fermentation method for the production of cocoa vinegar.ABSTRAKCairan pulpa hasil samping fermentasi biji kakao berpotensi  sebagai bahan baku pembuatan cuka kakao, tetapi kadar asam asetat yang dihasilkan relatif rendah. Untuk itu, perlu dilakukan  upaya peningkatan kadar asam asetat antara lain dengan melakukan beberapa metode fermentasi lanjutan dengan variasi penambahan sumber karbon (gula dan alkohol) dan lama fermentasi. Tujuan penelitian ini adalah: (1) mengkaji pengaruh  penambahan gula, alkohol dan lama fermentasi pada metode  fermentasi lanjutan yang berbeda terhadap karakteristik cuka  kakao dan (2) menetapkan metode fermentasi lanjutan dan  lama fermentasi yang optimal untuk produksi cuka kakao dengan kadar asam asetat tertinggi. Metode fermentasi lanjutan yang  dilakukan terdiri dari 3 metode yaitu: fermentasi alkohol dan  asam asetat (2 tahap), fermentasi asam asetat (1 tahap), dan  fermentasi tanpa inokulum (alami). Rancangan percobaan pada  penelitian ini menggunakan Rancangan Acak Kelompok (RAK)  faktorial 2 faktor pada metode fermentasi 2 tahap dan 1 tahap, serta RAK faktor tunggal pada fermentasi alami. Faktor I pada  metode fermentasi 2 tahap yang menggunakan inokulum Saccharomyces cerevisiae dan Acetobacter aceti, adalah  penambahan gula 4 konsentrasi (4, 6, 8, dan 10 %), dan pada metode fermentasi 1 tahap, yang menggunakan inokulum  Acetobacter aceti, adalah penambahan alkohol 4 konsentrasi (6,  8, 10, dan 12 %), sedangkan faktor II lama fermentasi (0, 5, 10,  15, 20, dan 25 hari). Sementara itu perlakuan lama fermentasi pada metode fermentasi alami sama seperti pada  faktor II. Semua metode fermentasi dilakukan pada suhu kamar  dalam 2 kelompok. Hasil penelitian menunjukkan bahwa: (1)  karakteristik cuka kakao dan OD660 cairan pulpa dipengaruhi  oleh perlakuan penambahan gula dan lama fermentasi serta  interaksinya pada metode fermentasi 2 tahap dan oleh perlakuan penambahan alkohol dan lama fermentasi serta  interaksinya pada fermentasi 1 tahap, serta oleh perlakuan lama  fermentasi alami, dan (2) cuka kakao dengan kadar asam asetat  tertinggi masing-masing dihasilkan pada fermentasi 2  tahap dengan penambahan gula cenderung 6 % dalam waktu 25 hari (2,35 %), fermentasi 1 tahap dengan penambahan alkohol 10 % dalam waktu 20 hari (3,37 %), dan fermentasi alami dalam  waktu 15 hari (2,65 %). Dengan demikian metode fermentasi 1  tahap dengan penambahan alkohol 10 % menggunakan  inokulum Acetobacter aceti dalam waktu 20 hari merupakan metode fermentasi lanjutan yang paling optimal untuk produksi cuka kakao.